Cuidados de enfermería en adultos con VIH-SIDA. Ecuador, 2018 - Díaz Colcha, Viviana Lisett (2019)
The Human Immunodeficiency Virus (HIV) is the infectious disease with repercussion in the biological, social and economic order, in alarming dimensions together with the progression and final stage of the disease the Acquired Immune Deficiency Syndrome (AIDS), being the constant concern for governments and health authorities in the country, which is why in the present investigation it was possible to identify nursing care in adults with HIV-AIDS in Ecuador and then describe the disease from primary, secondary and tertiary prevention. The methodology of this research is characterized by a bibliographic review of the literature with the assistance of different academic searchers, and a study population of 90 bibliographic references with a high level of updating was established, and the selection sampling technique was used to establish a sample of 70 articles that were analyzed in detail, at the end it is expected to establish related aspects or coincidence between the authors studied, among them adherence to treatment, stigmatism, anxiety that are based on nursing diagnoses applied to the direct and specific care of the patient, with a focus on the family, the social, cultural, psychological and spiritual.